SH2 domain‐containing protein tyrosine phosphatase‐2 is enriched in eyelid specimens of rosacea. Issue 1 (17th November 2022) - Chebolu, Apoorv; Ramos, Ramon Bossardi; Arunachalam, Thilaka; Adam, Alejandro Pablo; Wladis, Edward J.
Abstract: Background: Rosacea is a cutaneous disease that may secondarily affect the ocular surface. Due to the vision threatening, cosmetic, psychological, and work productivity impact, the identification of cellular targets that govern rosacea would enhance our understanding of the biology of the disease and delineate targets for therapeutic manipulation. Objective: To characterize the involvement of SH2 domain‐containing protein tyrosine phosphatase‐2 (SHP2) in the pathogenesis of rosacea. Methods: Specimens from elective ectropion surgery ( n  = 20) were processed from patients with rosacea ( n  = 10) and control patients ( n  = 10). Immunohistochemistry (IHC) and quantitative western blotting (WB) were performed to identify and quantify the presence of SHP2 and 4G10 (a phosphotyrosine antibody) in rosacea compared to normal tissue. IHC samples were graded according to an intensity scale (0–4). Mann‐Whitney statistical analyses were performed via a dedicated computerized software package. Results: On WB, SHP2 was expressed in higher concentrations in rosacea specimens ( p  < 0.05). On IHC, SHP2 was enriched in the epidermis in rosacea ( p  < 0.05), although 4G10 levels were not statistically significantly different between the two groups ( p  > 0.05). Conclusions: SHP2 is enriched in cutaneous specimens of rosacea, suggesting a critical role for this protein in the disease and indicating a modifiable therapeutic moiety. Abstract : Rosacea is an inflammatory disorder with devastating secondary ocular surface effects. SH2 domain‐containing protein tyrosine phosphatase‐2 (SHP2) is enriched in rosacea samples, which furthers our understanding of its inflammatory pathogenesis. SHP2 is a potential target for future clinicians aiming to develop therapeutics for rosacea.